Peran Digital Marketing Dalam Upaya Pengembangan UMKM “Jajan Burger” Di Kota Surakarta - Noviana Intan KP; Suprayitno Suprayitno; Syahrial Yoppi (Society : Jurnal Pengabdian Masyarakat, 2023)
Technological developments make digital marketing superior for increasing the sales of a business. The "Jajan Burger" business tries to take advantage of this opportunity to expand its market share. The purpose of this article is to find out how to implement or apply Gojek digital marketing applications to small and medium businesses "Jajan Burger". The method used is in the form of preparation before starting a business, implementing digital marketing, and evaluating. The result of this research is that digital marketing can make sales prospects for "Jajan Burger" increase and be better known by many people.